Novel insights on post-translational modifications of nucleic acid methylation proteins in hepatic fibrosis - Wen-Jie Sun; Ming-Hui Li; Yang Yang; Qi-Qi Dong; Hui Tao; Chao Lu; Jing-Jing Yang (Pharmacological Research)
Hepatic fibrosis is a pathologic state in which there is an excessive accumulation of the extracellular matrix (ECM) components within the liver parenchyma. It is an ongoing process that compromises the structure and functional performance of the liver tissue. Without treatment, it may progress to end-stage liver disease, including cirrhosis and hepatocellular carcinoma. The pathogenesis of hepatic fibrosis involves complex interactions between activated hepatic stellate cells (HSCs), inflammatory mediators, and angiogenic factors, which are regulated by epigenetic modifications and aberrations in signaling pathways. Recent advances highlight the emerging role of post-translational modifications (PTMs) of nucleic acid methylation protein regulators in the pathogenesis of hepatic fibrosis. These modifications affect gene expression and are critical in the development of hepatic fibrosis. This article recapitulates the existing research evidence, analyses the roles of DNA and RNA methylation, as well as their protein regulator PTMs, in hepatic fibrosis, and explains the impact of these modifications on hepatic fibrosis progression. Besides, this article considers the promising implication of these findings to launch new therapeutic strategies, providing a new perspective and direction for treating hepatic fibrosis.